Topologically protected refraction of robust kink states in valley photonic crystals - Gao, Fei (2019)
Recently discovered1,2 valley photonic crystals (VPCs) mimic many of the unusual properties of two-dimensional (2D) gapped valleytronic materials3,4,5,6,7,8,9. Of the utmost interest to optical communications is their ability to support topologically protected chiral edge (kink) states3,4,5,6,7,8,9 at the internal domain wall between two VPCs with opposite valley-Chern indices. Here we experimentally demonstrate valley-polarized kink states with polarization multiplexing in VPCs, designed from a spin-compatible four-band model. When the valley pseudospin is conserved, we show that the kink states exhibit nearly perfect out-coupling efficiency into directional beams, through the intersection between the internal domain wall and the external edge separating the VPCs from ambient space. The out-coupling behaviour remains topologically protected even when we break the spin-like polarization degree of freedom (DOF), by introducing an effective spin–orbit coupling in one of the VPC domains. This also constitutes the first realization of spin–valley locking for topological valley transport.